The Influence of Leadership, Work Culture, and Competencies on Commitment and Implications on Performance Private College Lecturer in Makassar City - Muhammad, Natsir (Lembaga Penerbitan dan Publikasi Ilmiah Program Pascasarjana IAI Sunan Giri Ponorogo, 2025)
This study investigates the impact of leadership, work culture, and competency on lecturer commitment and their combined effect on lecturer performance at private universities in Makassar City. The objectives include 1) analyzing the influence of leadership, work culture, and competency on commitment; 2) examining their direct effects on lecturer performance; and 3) exploring how commitment mediates the relationship between these factors and lecturer performance. Using a sample of 100 lecturers from management programs at accredited institutions, the study applies SEM analysis to assess validity, reliability, and the structural relationship between variables. Results indicate that while leadership has an insignificant effect on commitment, work culture and competency significantly enhance lecturer commitment. Moreover, lecturer commitment significantly improves performance, explaining 62.8% of its variation. These findings highlight the importance of fostering effective work cultures and enhancing competencies to boost commitment and performance in higher education settings.